Políticas culturais em cidades turísticas brasileiras: um estudo sobre as técnicas de vida contemporâneas - Silva, Rodrigo Manoel Dias da (Universidade do Vale do Rio dos Sinos, 2012)
The present paper is a study of the emergence, visibility and operation of life techniques that order and allow the agency of social actors in relations that produce cultural policies in Brazilian touristic cities. In this sense, the paper investigates the situation of cultural projects linked to institutional changes undergone by culture public policies in Brazil, and examines how cultural agents, at the level of their individual trajectories and collective possibilities, have taken actions to obtain resources and negotiated the design and implementation of projects. From a situational analysis, it has been found that such techniques become a condition for both the actors action and the formulation of projections, since they set determinants for the resource agency, thus constituting standards in social-historical scenarios of pluralization of those actions. Therefore, it has been described that State cultural agencies, individual agencies and social-formative agencies would be operativity standards of those techniques in the cultural policies studied. Finally, it has been noticed that the context of fragilization of institutional devices challenges cultural policies in our time by offering the irradiation of multiple cultural agencies, since, paradoxically, on the one hand, it builds a competitive field between projects and cultural actors in search of several resources, but, on the other hand, it allows the reconfiguration of value standards directed towards the reconstruction of social meanings in the same policies.
Keywords: Políticas culturais; Agenciamentos; Técnicas de vida; Cidades turísticas; Cultural policies; Agencies; Life techniques; Touristic cities; ACCNPQ::Ciências Humanas::Sociologia